2000
DOI: 10.1111/j.1151-2916.2000.tb01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of Model Porous Ceramics

Abstract: The finite element method (FEM) is used to study the influence of porosity and pore shape on the elastic properties of model porous ceramics. The Young's modulus of each model was found to be practically independent of the solid Poisson's ratio. At a sufficiently high porosity, the Poisson's ratio of the porous models converged to a fixed value independent of the solid Poisson's ratio. The Young's modulus of the models is in good agreement with experimental data. We provide simple formulae which can be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
252
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(296 citation statements)
references
References 40 publications
(158 reference statements)
25
252
2
11
Order By: Relevance
“…Bounding theorems dictate limits on the elastic response of the collagen as a function of the mechanical response of the deoxycholate-treated construct (appendix A). Estimates like those of Ramakrishnan & Arunachalam (1993) and Monte Carlo simulations like those of Roberts & Garboczi (2000) incorporate specific void shapes, and predict that the modulus of a deoxycholate-treated construct will disappear at a void (cell) volume fraction sufficiently large that void clusters coalesce, eliminating continuity in the collagen. Accurate estimates do not exist for composites containing dense concentrations of ellipsoidal or spherical inclusions.…”
Section: (A) Analytical Techniquesmentioning
confidence: 99%
“…Bounding theorems dictate limits on the elastic response of the collagen as a function of the mechanical response of the deoxycholate-treated construct (appendix A). Estimates like those of Ramakrishnan & Arunachalam (1993) and Monte Carlo simulations like those of Roberts & Garboczi (2000) incorporate specific void shapes, and predict that the modulus of a deoxycholate-treated construct will disappear at a void (cell) volume fraction sufficiently large that void clusters coalesce, eliminating continuity in the collagen. Accurate estimates do not exist for composites containing dense concentrations of ellipsoidal or spherical inclusions.…”
Section: (A) Analytical Techniquesmentioning
confidence: 99%
“…The Poisson ratio ν of the porous layer was set to 0.22 (taken from literature for porous alumina [35]), the cap eccentricity R was set to 0.25 to obtain a cap yield surface neither too circular nor too steep, α (a small number used to define the transition yield surface) was set to 0.01 and W (the porous volume fraction) was set to 0.17. A preliminary calculation showed that variation of the friction coefficient f between the indenter and the sample surface had negligible effect on the results and f was set to 0.1.…”
Section: Numerical Analysismentioning
confidence: 99%
“…In particular surface defects have a strong influence on their strength [32]. Furthermore, even a moderate porosity can have a substantial impact on their elastic modulus, strength and resistance to contact damage [33][34][35]. Finally, zirconia-containing ceramics require special attention: the tetragonal to monoclinic phase transformation, which accounts for their exceptional toughness, can occur spontaneously at low temperature in the presence of water, potentially deteriorating the material properties [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…dν eq = 0, see (20), (21). Earlier in [22] also it has been discussed that at sufficiently high porosity Poisson's ratio converges to a fixed non-zero value, irrespective of the matrix Poisson's ratio. Mentioned limiting behavior of equivalent Poisson's ratio is illustrated on Fig.3,4,5,6 and could be seen directly from the analytical results, presented for cases I-IV by equations (23),(29),(35),(41), respectively.…”
Section: Size -Sensitive Dem Theory In Case IVmentioning
confidence: 99%